Development and evaluation of an educational tool for barangay health workers in the City of Manila regarding over-the-counter drugs use in children ages 2 to 12 years old - Miniano, Ma. Kristina Bernadette B.​; Padilla, Aika Patriz P.​; Sendito, Maria Jennylyn V.​
BHWs play an important role as primary healthcare providers in the community. One of their responsibilities is the provision of health-related information, making it necessary for them to be knowledgeable. The purpose of this study is to design and evaluate an educational booklet for BHWs on the use of OTCs in children ages 2 to 12 years old. A focus group discussion was initially conducted with BHWs to determine gaps in the current knowledge of OTCs. A booklet was created based on the collected information. The booklet developed was then distributed to the BHWs in Manila. A pretest post test questionnaire was administered to the BHWs to determine its effect on knowledge. The respondents were also asked about their satisfaction on the booklet. Data was analyzed using Microsoft Excel and STATA 13.0 software. Majority of the BHWs are aged 50 - 59 years old (33.56%). Most were college undergraduates (35.57%) with previous occupations in the health care sector (53.02%) and nearly half had 3 to 4 children (40.94%). The BHWs' roles in the community included counseling with patients. Their knowledge on the common OTCs used in children was identified to be inadequate. The observed pretest score and post test score were 36.78% and 58.3%, respectively. After the intervention, there was an observed 21.56% difference in the mean total scores of the BHWs. Subjective and objective evaluation of the educational booklet showed percentage scores were higher than 90. The developed educational booklet was effective in increasing the knowledge of BHWs. Results show that it has a great potential to be implemented and used in a greater number of BHWs in different communities. Therefore, it is recommended to include more OTCs to make it more comprehensive. Further research is also necessary to improve the features of the tool and determine its effect on behavior, attitude and practices of BHWs.